EFEKTIVITAS PEMBELAJARAN BAND PADA KEGIATAN EKSTRAKURIKULER TERHADAP KREATIVITAS SISWA DI SMA NEGERI 2 SIBORONGBORONG - Kalep Ompusunggu; Testi Bazarni Zebua; Novita Aditya Manalu; Robert KA Simangunsong; Aprinaldi P.Simarangkir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The study aims to describe band learning in extracurricular activities on students' creativity at SMA Negeri 2 Siborongborong. This study is motivated by the problem of students' lack of understanding of measures, tempo, melody, rhythm, and harmony in band performance during extracurricular activities. This limited understanding has the potential to affect the accuracy of performance, group cohesiveness, and overall performance quality. This study uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The results of the study indicate that effective band learning shows improvements in musical cohesion, the emergence of creative ideas, confidence in performing, as well as the ability to express music through band performance. Through this activity, students not only learn to play musical instruments but also learn to cooperate, practice discipline, and express creative ideas in the form of harmonious band music performance. Based on this, it can be concluded that band learning in extracurricular activities at SMA Negeri 2 Siborongborong creates an enjoyable learning atmosphere, which ultimately has a positive impact on students' motivation and interest in participating in music art learning.